The Role of Project-Based Learning in Developing the Professional Culture of Future Art Teachers - Muzropova Guljamol Mardonovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the role of project-based learning in developing the professional culture of future art teachers. Professional culture encompasses the knowledge, skills, attitudes, and ethical standards necessary for effective teaching and engagement in the field of art education. Project-based learning (PBL) provides a dynamic pedagogical approach that promotes active engagement, creativity, problem-solving, and collaboration, thereby enhancing the professional development of art teacher candidates. The study highlights how project-based learning fosters practical competencies, cultural awareness, and reflective practice in future educators. By working on creative projects, analyzing artistic problems, and producing tangible outcomes, students develop critical thinking, organizational skills, and professional responsibility. The article emphasizes that integrating PBL into art teacher education strengthens both pedagogical skills and the overall professional culture, preparing future educators to navigate complex educational environments and to cultivate creativity and cultural literacy in their students.